2022
DOI: 10.7150/ijbs.69460
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and gender differences in older adults in Hong Kong during the COVID-19 pandemic: a network analysis approach

Abstract: Background:The 2019 novel coronavirus disease (COVID-19) outbreak had a detrimental impact on the mental health of older adults. This study evaluated the central symptoms and their associations in the network of depressive symptoms and compared the network structure differences between male and female older adults in Hong Kong. Methods: Altogether, 3,946 older adults participated in this study. We evaluated the centrality indicators for network robustness using stability and accuracy tests, and examined the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
5
9
0
1
Order By: Relevance
“…"Sad mood" (PHQ2) was the most central symptom in the depression network model among Macau residents during the 618 COVID-19 wave, which is consistent with the previous findings in a German general population study (Hartung et al, 2019) and in a study of older adults in Hong Kong (Jin et al, 2022) during the COVID-19 pandemic. According to the Diagnostic and Statistical Manual of Mental Disorder-5 (DSM-5) (APA, 2013), "sad mood" is a core symptom of major depressive disorder (MDD), and persistent sadness is also a risk factor for depression (Wolff, 1999;Davidson and Henriques, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…"Sad mood" (PHQ2) was the most central symptom in the depression network model among Macau residents during the 618 COVID-19 wave, which is consistent with the previous findings in a German general population study (Hartung et al, 2019) and in a study of older adults in Hong Kong (Jin et al, 2022) during the COVID-19 pandemic. According to the Diagnostic and Statistical Manual of Mental Disorder-5 (DSM-5) (APA, 2013), "sad mood" is a core symptom of major depressive disorder (MDD), and persistent sadness is also a risk factor for depression (Wolff, 1999;Davidson and Henriques, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…Network analysis could help determine nodes that are the most central (influential) in the network model and could be targeted for prevention and intervention ( Borsboom and Cramer, 2013 ; Cramer et al, 2016 ; Marchetti, 2019 ). In the past years network analysis has been widely applied in different populations during the COVID-19 pandemic such as adolescents ( Cai et al, 2022a ), the general population ( Cheung et al, 2021 ; Zavlis et al, 2021 ), older people ( Jin et al, 2022 ), college students ( Bai et al, 2021 ), clinicians ( Cai et al, 2022c ), and psychiatric patients ( Kim et al, 2022 ). Evidence showed that the pattern and clinical features of depression were highly dependent on the socioeconomic context ( Kleinman, 2004 ; Compton et al, 2006 ); therefore, the network structure of the depressive symptoms should be examined separately for the population living in areas with different socioeconomic contexts ( Cheung et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The node “Energy” was another significant central symptom in the depression network model, consistent with previous findings reported in community-dwelling older adults ( 66 ), patients with major depressive disorder ( 67 ) and adult Hong Kong residents ( 60 ). Older adults with pacemaker implantation may experience disturbances in sleep and appetite that influence energy levels ( 68 ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, it was suggested that the fear of contagion and the simultaneous feeling of being a burden to the younger generation because of being severely limited socially had a pessimistic influence on individuals' thoughts about their future and may have reinforced thoughts of death. Some studies found that there is a higher prevalence of anxiety, depression, and loneliness in older adults when compared with prepandemic levels ( Bankole, 2022 ; Jin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%